A core–shell Si@Nb2O5 composite as an anode material for lithium-ion batteries. Issue 46 (20th April 2016) - Wang, Guanqin; Wen, Zhongsheng; Du, Lulu; Li, Song; Ji, Shijun; Sun, Juncai
Abstract : Si@Nb2 O5 with high electrochemical stability is fabricated via solvothermal method with silicon nanoparticle and NbCl5 as the precursors in ethyl alcohol. Abstract : Silicon has received intense attention due to its high theoretical capacity for lithium storage. However, its poor cycling stability limits its commercial application due to its dramatic volumetric shrinking and expanding in the crystal lattice during the lithiation and de-lithiation process. In the study, a Si@Nb2 O5 nanocomposite is successfully fabricated via a facile solvothermal method with silicon nanoparticles and niobium chloride as the precursors. The coating layer of Nb2 O5 improves the electrochemical stability on cycling dramatically. The high reversible capacity and the excellent cycling performance of the Si@Nb2 O5 nanocomposite are demonstrated, with a retained specific capacity of up to 2256.4 mA h g −1 after 80 cycles and a coulombic efficiency approaching 99%.